Variation of Arteries Forming Circle of Willis in Adult Human Cadavers - Gautam, Jyoti; Adhikari, Bidur; Bhandari, Rosha; Shrestha, Anusuya; Ranjit, Nirju (Journal of Institute of Medicine Nepal, 2020)
Introduction Circle of Willis is a large arterial anastomosis between internal carotid and vertebrobasilar arterial system. It is the principal collateral channel for constant blood flow to brain. Any changes in its morphology may cause vascular insufficiency of variable severity. Knowledge about its anomalies may elucidate occurrence of cerebrovascular disorders, its presentation, treatment, prognosis and prevention.MethodsAn observational study on 107 fresh cadavers was conducted at Maharajgunj Medical Campus from September 2016 to August 2017. After dissection of the scalp and removal of the vault and dura mater, the brain was obtained. Then the Circle of Willis was identified and observed for its completeness, symmetry, presence, origin and number of arteries forming it and the obtained data were documented, photographed and analyzed.ResultsOut of 107 cadavers, variations were noted among 15 (14%): out of which 10 were male and 5 female. Twelve cadavers had single variation while 3 had two variations. Accessory anterior cerebral artery was found in 7 (38.90%), fetal origin of right posterior communicating artery in 2 (11.10%), fetal origin of left posterior communicating artery in 4 (22.20%), early bifurcation of left posterior cerebral artery in 1 (5.60%), variant anterior communicating artery in 2 (11.10%), fused anterior cerebral artery in 1 (5.60%) and aneurysm in 1(5.60%) subjects were found.ConclusionVariations were noted among 15 cadavers (14%), 12 cadavers had single variation while 3 had two variations. The most common variation seen was accessory anterior cerebral artery found in 7 cadavers (38.90%). Most of the variations were found in midline anteriorly followed by right side.